(untitled) (Latakia University Journal -Biological Sciences Series, 2023)
This study aimed to assess the change in the spatial distribution of the risk of water erosion in the Qordaha Basin using CORINE model for the period 2014-2020. Corine model depend on calculating all factors that affect water erosion such as soil erodibility, erosivity, slope and land cover parameters. Soil erodibility was evaluated through estimating (soil texture, soil depth, and stoness percentage), These indicators were classified according to the degree of their impact on soil erosion, and then a map was prepared for each of these indicators. From the results of these maps, a map of the Soil erodibility . The slope which was prepared from using DEM and the rainfall erosivity index was calculated by collecting the monthly precipitation amounts for the period 2014-2020 and the average temperature for the same period from the meteorological station in Qardaha, and the type of land cover period 2014-2020 was classified into two classes by the degree of protection provided the soil, Then the final risk map was prepared through multiplication of these four factors for the entire study area. The study showed that 64.01% of the studied area had a severe potential risk of soil erosion, while the potential risk was moderate in 16.36% of the area of the studied area, while the percentage of the area of areas with low potential risk was (19.63%) of the area of the study area. The role of land cover in reducing the risk of erosion, as the percentage of areas classified as very dangerous in the potential risk map decreased from 64.01% to 35.74.% in the actual risk map. The reduction rate has decreased( 31%) in 2020 due to the deterioration of vegetation cover due to fires that have been exposed to forests and intense human activities, to the concentration of the risk of severe erosion in the western and southeastern regions.